Rancang Bangun Detektor Gerak Menggunakan Infra Merah Dengan Memanfaatkan Layanan Sms Pada Telepon Seluler Berbasis Mikrokontroler AT89S52 - Widiyatmoko, Anjar; Sumariyah, Sumariyah (BERKALA FISIKA, 2009)
A infrared movement detector using Short Message Service based on AT89S52 microcontroller has been designed and realized. The detector can be used for monitoring any passing object in the room. This research can be used to detect up to four object in the different room. The detector was consisted one control station and one receiver station. The control station used four couple of infrared transmitter and receiver. The receiver station of mobile station was used to receive message from control station. This detector was consisted of hardware and software. The hardware was designed with infrared transmitter, an 38 kHz infrared sensor, an op-amp comparator used to compare infrared sensor output voltage. The Transmitter emitted infrared ray and received by sensor. Any moving object passed between them producing the output voltage of infrared receiver change and proceed to comparator resulting high output. This high output signal used as trigger event to running sending message procedure. And the designed software for microcontroler was written in C language. The research showed the passed object passed infrared transmitter can be detected is received and the SMS by mobile station is matched as the location of passing object through the infrared sensor. Keywords: Short Message Service, Microcontroller, Infrared